2019
DOI: 10.1038/s41598-019-39169-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of a prophage-encoded glycocin and its immunity protein suggests a mutualistic strategy of a phage and its host

Abstract: Sublancin 168 is a highly potent and stable antimicrobial peptide secreted by the Gram-positive bacterium Bacillus subtilis . Production of sublancin gives B . subtilis a major competitive growth advantage over a range of other bacteria thriving in the same ecological niches, the soil and plant rhizosphere. B . subtilis protects itself against sublancin by producing the cognate immunity protein Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Based on comparison of the sizes and integration sites of prophage elements within Bacillus sp., SPβ and phi3T clearly belong to a distinct prophage group. These phages appear extremely large (2-3-fold larger than average prophages), and they possess sophisticated communication systems that are potentially capable of sensing the frequency of lysogenized hosts [65,88] or biosynthetic gene clusters [89,90], and functional genes related to host dormancy [91,92]. A high level of homology between SPβ and phi3Ts offers extensive regions for homologous recombination, which can be additionally promoted by the recombination machinery involved in natural competence [93] and in non-homologous end-joining repair [94] .…”
Section: Discussionmentioning
confidence: 99%
“…Based on comparison of the sizes and integration sites of prophage elements within Bacillus sp., SPβ and phi3T clearly belong to a distinct prophage group. These phages appear extremely large (2-3-fold larger than average prophages), and they possess sophisticated communication systems that are potentially capable of sensing the frequency of lysogenized hosts [65,88] or biosynthetic gene clusters [89,90], and functional genes related to host dormancy [91,92]. A high level of homology between SPβ and phi3Ts offers extensive regions for homologous recombination, which can be additionally promoted by the recombination machinery involved in natural competence [93] and in non-homologous end-joining repair [94] .…”
Section: Discussionmentioning
confidence: 99%
“…In the same context, a single gene (asmH) has been suggested to be responsible for the immunity to ASM1 [8]. Denham et al [25] reported that sunI is responsible for encoding the immunity protein for sublancin 168. ThuI is a putative immunity protein detected in the thurandacin gene cluster [6].…”
Section: Discussionmentioning
confidence: 99%
“…Based on comparison of the sizes and integration sites of prophage elements within Bacillus sp., SPβ and phi3T clearly belong to a distinct prophage group. These phages appear extremely large (2-3-fold larger than average prophages), and they possess sophisticated communication systems that are potentially capable of sensing the frequency of lysogenized hosts [64, 87] or biosynthetic gene clusters [88, 89], and functional genes related to host dormancy [90, 91]. A high level of homology between SPβ and phi3Ts offers extensive regions for homologous recombination, which can be additionally promoted by the recombination machinery involved in natural competence [92] and in non-homologous end-joining repair [93].…”
Section: Discussionmentioning
confidence: 99%